1996
DOI: 10.1097/00007890-199605150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcome of Orthotopic Liver Transplantation for Chronic Hepatitis B Cirrhosis With Aggressive Passive Immunization

Abstract: Passive immunization with hepatitis B surface antibody (anti-HBs) is important to prevent hepatitis B virus (HBV) recurrence after orthotopic liver transplantation for chronic HBV cirrhosis. Hepatitis B immune globulin (HBIG) dosing regimens have been poorly defined, utilize numerous routes of administration, and result in a high rate of HBV relapse and mortality. Twenty-five of 27 (93%) patients transplanted (four retransplants) for chronic HBV cirrhosis show no evidence of recurrent HBV (range, 2-55 months).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
197
1
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(212 citation statements)
references
References 20 publications
9
197
1
5
Order By: Relevance
“…Other investigators have reported that a fixed dose regimen of HBIG may be insufficient to maintain constant titers of anti-HBs in these patients. 18 Two of the three patients who had no S mutation post-OLT were hepatitis B e antigen-and HBV-DNA-positive (by hybridization assay) pre-OLT, and were reinfected shortly after (1 and 2 months) transplantation. Reinfection in these patients may have occurred because of inadequate neutralization of circulating virus or release of virus from extrahepatic reservoirs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other investigators have reported that a fixed dose regimen of HBIG may be insufficient to maintain constant titers of anti-HBs in these patients. 18 Two of the three patients who had no S mutation post-OLT were hepatitis B e antigen-and HBV-DNA-positive (by hybridization assay) pre-OLT, and were reinfected shortly after (1 and 2 months) transplantation. Reinfection in these patients may have occurred because of inadequate neutralization of circulating virus or release of virus from extrahepatic reservoirs.…”
Section: Discussionmentioning
confidence: 90%
“…Thirteen patients (patients 1-13) became HBsAg-positive again while they were still receiving HBIG; 7 (patients [14][15][16][17][18][19][20] became HBsAg-positive after discontinuation of HBIG. Reinfection occurred after a mean of 8.5 Ϯ 1.5 months (range, 1-20 months) post-OLT.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, only 2 of 27 patients (7%) became reinfected with HBV, but in a subsequent analysis, 9 of 39 patients (23%) developed allograft infection despite an increase in minimum target levels of anti-HBs to 500 IU/L for the first 6 months and 150 IU/L thereafter. 16,22 HBIG use continues to be limited by breakthrough reinfection in 10% to 20% of cases. 23 The mechanism by which HBIG monotherapy controls the recurrence of disease is poorly understood.…”
Section: Hbigmentioning
confidence: 99%
“…Subsequently, the use of high doses of intravenous (IV) hepatitis B immune globulin (HBIG) after OLT reduced HBV recurrence and improved survival. [5][6][7][8][9][10][11][12] Investigators of the European Concerted Action of Viral Hepatitis project 5 reported a 75% rate of HBV recurrence after OLT in patients receiving no prophylaxis or very short-term HBIG treatment and a 33% rate in patients receiving long-term HBIG prophylaxis. The benefit appeared to be greatest among patients with negative HBV DNA and hepatitis Be antigen (HBeAg) before OLT.…”
Section: Copyright 1999 By the American Association For The Study Of mentioning
confidence: 99%
“…13,14 Furthermore, reinfection of the graft by HBV may still occur despite IV HBIG. [5][6][7][8][9][10][11][12] Graft reinfection may be caused by inadequate neutralization because of overwhelming amounts of HBV or break-through infection by escape HBV surface protein mutants. 15,16 Recently, long-term survival and HBV recurrence data using IV HBIG prophylaxis were reported by Samuel et al 17 Excluding patients with delta hepatitis and fulminant liver failure, 89 patients with HBV cirrhosis underwent OLT.…”
Section: Copyright 1999 By the American Association For The Study Of mentioning
confidence: 99%